OPTIMASI PERENCANAAN PRODUKSI PENJUALAN HIJAB MENGGUNAKAN METODE FUZZY LINIER PROGRAMMING - Indriana Putri Solehah; Laila Fitriana (Journal of Mathematics and Mathematics Education, 2018)
Abstract:Currently, hijab is very interesting thing in the community. Seeing from the many uses of hijab by Muslim women, the production of hijab is adjusted to those needs. The problem faced by hijab producers is how much hijab will be made with all constraints and limitations. One method that can be used for optimization of production planning is Fuzzy Linear Program and LINDO Program. Fuzzy Linear Program is a linear program method that is applied in a fuzzy environment, while the LINDO program is a program designed to solve linear cases of programming which use certain formats to be processed by LINDO program. From the above problems, the authors solve this hijab production problem using Fuzzy Linear Programming to determine the right number for each model with maximum profit.Keywords:Hijab, Fuzzy Linear Programming, Simplex Method, LINDO.